Development and Characterization of a Sustainable and Vegan Lip Balm Utilizing Soybean Oil and Carnauba Wax: Pengembangan dan Karakterisasi Lip Balm Berkelanjutan dan Vegan yang Menggunakan Minyak Kedelai dan Lilin Carnauba - Subara, Deni; Rukmana, Fitri Hardiyanti; Afifah, Amalia (Universitas Brawijaya, 2025)
The demand for organic cosmetics, including lip balms, is increasing. While soybean oil and carnauba wax are known for their beneficial properties in cosmetics, their specific combination in a lip balm formulation has not been previously explored. This study aimed to determine the optimal lip balm formulation from a combination of soybean oil and carnauba wax and to analyze the effect of varying formulations on the product's physicochemical characteristics. The lip balms were prepared using a melt-and-mix method. Physicochemical properties (pH, melting point, adhesion time, loss on drying and greasiness) were evaluated according to the Indonesian National Standard (SNI) 16-4399-1996. A Non-Factorial Completely Randomized Design (CRD) was employed, and the data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT). Results indicated that the formulation significantly affected (p<0.05) the melting point, adhesion time, greasiness and loss on drying but did not significantly affect the pH. Formulation 5 (F5) was selected as the optimal formulation, exhibiting the following characteristics: a pH of 6.206, a melting point of 66.00 °C, an adhesion time of 9.00 seconds, loss on drying (LoD) 0.043% and greasiness 8.20 cm. Furthermore, hedonic testing revealed that F5 was the formulation most preferred by panelists. In conclusion, the combination of soybean oil and carnauba wax can yield a natural lip balm with desirable properties and high consumer acceptability, with F5 identified as the optimal formulation in this research.